Studi Deskriptif Mengenai Komunikasi Persuasif Pegawai dalam Menangani Keluhan Pelanggan di Perusahaan Daerah Air Minum Tirta Bumi Wibawa Kota Sukabumi: Studi Deskriptif Mengenai Komunikasi Persuasif Pegawai dalam Menangani Keluhan Pelanggan di Perusahaan Daerah Air Minum Tirta Bumi Wibawa Kota Sukabumi - Yanti Lestari Pujiastuti (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
Every product or service company that competes in the marketing order is increasingly numerous and diverse, resulting in competition among companies to meet the desires of consumers and provide service satisfaction to consumers. One of the actions to provide satisfaction to consumers is to provide services for consumers preferably because in essence the purpose of the business is to make consumers satisfied. Persuasive communication can be used as a direction of where and how the survival of a company, this is because one of the supports for the progress of a company depends on the balance of internal and external communication of the company. The approach taken in this research is to use a qualitative approach with descriptive methods. In arguing and showing evidence, an employee is required to have good intelligence. One of them is the intelligence of dealing with consumer complaints. Regarding the psychological attractiveness of an employee in customer relations, of course, it is important, such as verbal communication which is an attraction in handling customer complaints. verbal communication used by Company employees is good. In relation to the appeal of credibility in handling customer complaints at the Regional Drinking Water Company Tirta Bumi Wibawa Kota Sukabumi, it is clear and in accordance with the situation in the community, seen from the appearance and responses of customers who have made complaints to the head office and used as informants in this study.